Competition policy for online platforms' self-preferencing conducts - Min Jung Kim (Korea Development Institute (KDI), 2024)
Self-preferencing by online platforms encompasses a spectrum of conduct types, all with implications for both anti-competitive and pro-competitive effects. Therefore, it is desirable to maintain the current ex-post regulatory framework, which applies the rule of reason and intervenes only when such practices are deemed to be unjust or harmful to fair competition, rather than imposing a blanket ban. However, the timeliness and efficiency of enforcement mechanisms should be improved in light of the distinct characteristics of the online environments and self-preferencing conducts.
Keywords: 330